2015
DOI: 10.1530/rep-14-0587
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and ovarian oestradiol and the variability in the LH surge induced in ewes by the ram effect

Abstract: The proportion of anoestrous ewes ovulating after exposure to a sexually active ram is variable mainly due to whether an LH surge is induced. The aim of this study was to determine the role of oestradiol (E 2 ) in the ram-induced LH surge. In one study, we measured the plasma concentrations of E 2 in ewes of different breeds before and after the 'ram effect' and related these patterns to the presence and latency of the LH surge, while another compared ovarian responses with the 'ram effect' following exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
7
0
4
Order By: Relevance
“…The normal LH surge is essential for ovulation. Without this surge, sheep will not spontaneously ovulate, enter oestrus or generate a corpus luteum (Fabre-Nys et al, 2015;Muñoz et al, 2012). Inhibited LH signalling has been shown to suppress early luteal angiogenesis which is essential for normal luteal development and function (Brown, Fabre, Cognie, & Scaramuzzi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The normal LH surge is essential for ovulation. Without this surge, sheep will not spontaneously ovulate, enter oestrus or generate a corpus luteum (Fabre-Nys et al, 2015;Muñoz et al, 2012). Inhibited LH signalling has been shown to suppress early luteal angiogenesis which is essential for normal luteal development and function (Brown, Fabre, Cognie, & Scaramuzzi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This socio-sexual stimulation is often referred to as the “ram effect”. In most ewes this male-induced LH surge is preceded by a sustained increase in the plasma concentration of oestradiol lasting between 8 and 56 hours [ 29 ] and is similar to the reproductive neuroendocrine events seen in cyclic ewes during the breeding season [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The causes of these early LH surges have not been studied. In our laboratory precocious LH surges were seen in about 15% Ile-de-France and Mérinos d’Arles ewes [ 26 , 29 ] and as happens with “normal” LH surges, they induced ovulation [ 26 ]. The time interval 0–8 hours is much shorter than that observed when the LH surge is induced with exogenous oestradiol [ 6 , 9 ]; these LH surges occur too soon to be explained by the normal oestradiol-induced positive feedback mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, partly because of the difficulty in measuring the very low concentrations of circulating estradiol present during anestrus there has been very little experimental support for this hypothesis (Knight et al, 1978 ; Johnson et al, 2011 ). In a recent study we showed that, in all ewes the introduction of rams is followed by an increase in the circulating concentration of estradiol (Figure 2A , Fabre-Nys et al, 2015 ). In most anestrus ewes, the LH surge induced by the “ram effect” was preceded by increases in the circulating concentration of estradiol at least three-fold above the basal concentration for 14.5 ± 0.86 h (min 6 h; max 36 h, Figure 2B ).…”
Section: Role Of Estradiolmentioning
confidence: 64%
“…This variability in a highly seasonal breed, the Mouton Vendéen, is due to the low sensitivity of the ovary that releases very little amount of steroids in response to stimulation by a ram. The granulosa cells of these ewes in culture, also have a low response to in vitro stimulation by IGF-I and FSH and reduced expression of StAR (Fabre-Nys et al, 2015 ). In other breeds such as the Romane the frequency and latency of the LH surge is variable, although the quantities of estradiol secreted after the “ram effect” do not differ from those in breeds such as the Mérinos d'Arles and Ile de France that respond well to it.…”
Section: Role Of Estradiolmentioning
confidence: 99%